(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article is dedicated to one of the important national issues of translation studies – translation interpretation of Abay’s poems. To date we have translated many poems of Abay Kunanbaev by different translators from different countries. However, there are a few works devoted to the transfer of the author’s style. In the 160th anniversary of Abay in Almaty there has released a unique book «Twenty poems of Abay», which included various versions of translations of his poems, taken at different times to different poets and translators. Adibaev Marat Khasenovich – translatorbilingual, being the compiler of this book, completed a new translation of twenty poems of Abay from the original text into Russian, maintaining individual style and the author’s intent. However, these translations are still not explored, which determines the relevance of this theme. The article presents the post-translation analysis of several poems of Abay. In the conclusion there is the scientific assessment to quality of the new translations of M. Adibayev